Sagot :
Answer:
1. 2(2)+(13-9(2))
4+(13-18)
4+(-5)
-1
2.3+6(2)/3
3+12/3
15/3
5
3.16(2)-32(1)+5
32-32+5
5
4.2(2)^3+4(-3)-7(47.5)
2(8)+(-12)-332.5
16-12-332.5
-328.5
5.5-4(2)+8(3)^2
5-8+8(3)
5-8+24
21
6. 4(-4)+5(-5)(-4)-12(-5)^2
-16+5(20)-12(25)
-16+100-300
-216
Answer:
1. -1
2. 7
3. 5
4. -328.5
5. 69
6. -216
Step-by-step explanation:
1. 2y+(13 - 9y) when y = 2
2(2)+(13-9(2)
4+(13-18)
4+ -5
= -1
2. 3 + 6b ÷ 3 when b is = 2
3+6(2)÷3
3+12÷3
3+4
=7
3. 16p - 32q + 5 when p = 2 and q=1
16(2)-32(1)+5
32-32+5
=5
4.2b³+4g-7a; b=2, g=-3, a=47.5
2(2)³+4(-3)-7(47.5)
2(8)-12-332.5
16-12-332.5
4-332.5
-328.5
5. v-4x + 8 a²; v = 5 and x =2, a = 3
5-4(2)+8(3)²
5-8+8(9)
5-8+72
-3+72
= 69
6. 4r +5xr - 12x²; r = -4 and x = -5
4(-4)+5(-5)(-4)-12(-5)²
-16+5(20)-12(25)
-16+100-300
84-300
=-216